The occlusion of sodium ions within the mammalian sodium-potassium pump: its role in sodium transport. - Glynn, I M (1984)
The hypothesis that the ADP-sensitive form of phosphorylated Na+, K+-ATPase contains occluded sodium ions has been tested by a procedure which involves (i) modifying the enzyme with alpha-chymotrypsin or N-ethylmaleimide (NEM) so that the ADP-sensitive form is more stable than it is in the native enzyme, (ii) phosphorylating the modified enzyme with ATP in the presence of labelled sodium ions, and (iii) forcing the phosphorylated enzyme rapidly through a cation-exchange column and measuring the labelled sodium in the effluent. The results show that ADP-sensitive phosphoenzyme prepared from alpha-chymotrypsin- or NEM-modified Na+, K+-ATPase is able to carry labelled sodium ions through a cation-exchange resin. This behaviour was not seen with native Na+, K+-ATPase or when phosphorylation was prevented by the omission of magnesium ions or by the substitution of adenylyl(beta, gamma-methylene)diphosphonate (AMP-PCP) for ATP. The occluded sodium ions were rapidly released when the phosphoenzyme was dephosphorylated by ADP. When alpha-chymotrypsin-modified enzyme was phosphorylated by ATP with 1 mM-sodium in the medium, close to three sodium ions were occluded per phospho group. The stoicheiometry at much lower sodium concentrations could not be determined satisfactorily. A consideration of the rate constants of the reactions thought to be involved in the occlusion of sodium and in the release of sodium from the occluded state shows that, so far as they are known, these constants are compatible with the hypothesis that the occluded-sodium form of the phosphoenzyme plays a central role in sodium transport through the pump.